Struktur Komunitas Makrozoobenthos di Ekosistem Mangrove Perairan Paru Keudee, Kabupaten Pidie Jaya - Nanda R. Janestia; Muhammad A. Sarong; Syahrul Purnawan (Universitas Syiah Kuala, 2017)
This study aimed to analyze the community structure of makrzoobenthos included density, diversity and uniformity. The research was conducted during October 2016 in the waters of village Paru Keudee sub District, Pidie Jaya District. The location was divided into three stations with five replications. Macrozoobenthos samples taken using the square transect method. Identification of macrozoobenthos was taken place at the Laboratory of Marine and Fisheries Faculty, and substrate type in Soil Laboratory, Faculty of Agriculture, University of Syiah Kuala. The results of the study were (1) the density of macrozoobenthos ranged from 35.6 ind/m2 to 58.2 ind/m2. Diversity index ranges from 2.42 to 2.63 and uniformity index ranges from 0.73 to 0.80. The highest density range of 35.6 ind/m2 to 58.2 ind/m2, while diversity of macrozoobenthos was categorized as moderate with highly uniformity of macrozoobenthos.Penelitian ini bertujuan untuk menganalisis struktur komunitas makrozoobenthos meliputi kepadatan, keanekaragaman dan keseragaman. Penelitian telah dilakukan pada bulan Oktober 2016 di Perairan Gampong Paru Keudee Kecamatan Bandar Baru Pidie Jaya. Dimana lokasi dibagi kedalam tiga stasiun dengan lima ulangan. Sampel makrozoobenthos diambil dengan menggunakan metode transek kuadrat. Identifikasi makrozoobenthos pada Laboratorium Fakultas Kelautan dan Perikanan, dan tipe substrat pada Laboratorium Tanah Fakultas Pertanian, Universitas Syiah Kuala. Hasil penelitian menunjukkan kepadatan makrozoobenthos berkisar 35,6 ind/m2 sampai 58,2 ind/m2. Indeks keanekaragaman berkisar 2,42 sampai 2,63 dan indeks keseragaman berkisar 0,73 sampai 0,80. Kepadatan tertinggi berkisar 35,6 ind/m2 sampai 58,2 ind/m2 sementara Keanekaragaman makrozoobenthos adalah sedang dan keseragaman makrozoobenthos adalah tinggi.